Childhood Secondhand Smoke Exposure and ADHD‐Attributable Costs to the Health and Education System. (October 2014) - Max, Wendy; Sung, Hai‐Yen; Shi, Yanling
ABSTRACT BACKGROUND Children exposed to secondhand smoke (SHS) have higher rates of behavioral and cognitive effects, including attention deficit hyperactivity disorder (ADHD), but the costs to the health care and education systems have not been estimated. We estimate these costs for school‐aged children aged 5‐15. METHODS The relative risk (RR) of ADHD from SHS exposure was obtained from our previous work. SHS exposure was measured using 2 alternative approaches—reported exposure and serum cotinine‐measured exposure. RRs and SHS exposure were used to determine the number of children with SHS‐attributable ADHD, and mean costs of ADHD‐related health care and education services were applied to obtain SHS‐attributable health care and education costs. RESULTS Annual health care costs of SHS‐attributable ADHD ranged from $644 million (using reported SHS exposure) to $2.05 billion (using cotinine‐measured exposure). SHS‐attributable costs to the education system ranged from $2.90 to $9.23 billion. CONCLUSIONS The costs of SHS‐attributable ADHD to the education system may total more than 4 times the costs for health care. The huge economic impact of SHS exposure on the education system has not been documented previously, and suggests that reducing childhood exposure to tobacco smoke will release substantial funds that could be used for general education of all children.